How Do You Know? : The Economics of Ordinary Knowledge - Hardin, Russell, 1940- (Book collections on Project MUSE., 2009)
How do ordinary people come to know or believe what they do? We need an account of this process to help explain why people act as they do. You might think I am acting irrationally--against my interest or my purpose--until you realize that what you know and what I know differ significantly. My actions, given my knowledge, might make eminently good sense. Of course, this pushes our problem back one stage to assess why someone knows or believes what they do. That is the focus of this book. Russell Hardin supposes that people are not usually going to act knowingly against their interests or other.